ANALISIS DAMPAK UTANG LUAR NEGERI TERHADAP PRODUK DOMESTIK BRUTO INDONESIA PERIODE 1988 – 2019 - Zainal Arifin H. Masri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This study aims to see the impact of foreign debt on Indonesia's gross domestic product (GDP). This study uses a combined method, qualitative research methods and quantitative research methods. Qualitative methods are used to describe descriptively the development of foreign debt and GDP in Indonesia. The method used to explain statistically / quantitatively the relationship and influence of foreign debt on GDP in Indonesia. The data analysis technique used in quantitative methods is a simple regression equation, correlation coefficient, coefficient of determination and hypothesis testing (t test). The sample used is time series data for the last 30 years from the variables of external debt and GDP. The results of data processing using SPSS show that foreign debt has a significant effect on gross domestic product. External debt has a very strong relationship with gross domestic product. The calculation results obtained by the linear regression equation Y = - 4,358,467,905 + 50,498,518X, none = 0.976, KD = 0.953 and Fcount = 568.018 with Sig F Change = 0.000